2005
DOI: 10.3917/cca.112.0109
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation des critères non financiers pour évaluer ou piloter la performance: analyse théorique

Abstract: Résumé :Les déterminants justifiant l'utilisation des critères non financiers pour évaluer ou piloter la performance renvoient à des explications théoriques en liaison avec les approches contractuelles et cognitives. L'objectif de notre article est de proposer pour ces deux approches une analyse théorique. Pour l'approche contractuelle, nous dressons une typologie des explications du choix des critères non financiers avancées dans les travaux existants. Nous montrons également que d'autres théories auraient pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…This finding is consistent with previous research (Chenhall, 2003;Chapman, 1997) and also substantiates the findings of Gordon and Miller (1976), who found that firms' decentralized structure goes along with a more diversified information system ensuring improved performance. In addition, Poincelot and Wegmann (2005) suggest a similar conclusion, as they showed that the content of BSCs would be more diversified in the most decentralized organizations. This result is explained by the proliferation of indicators when reporting is carried out in a context of increased delegation, as decentralization implies the use and aggregation of a greater number of indicators, especially financial and operational indicators.…”
Section: Findings Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…This finding is consistent with previous research (Chenhall, 2003;Chapman, 1997) and also substantiates the findings of Gordon and Miller (1976), who found that firms' decentralized structure goes along with a more diversified information system ensuring improved performance. In addition, Poincelot and Wegmann (2005) suggest a similar conclusion, as they showed that the content of BSCs would be more diversified in the most decentralized organizations. This result is explained by the proliferation of indicators when reporting is carried out in a context of increased delegation, as decentralization implies the use and aggregation of a greater number of indicators, especially financial and operational indicators.…”
Section: Findings Discussionmentioning
confidence: 56%
“…However, the theory suggests that non-financial criteria are often extensively used when the decision-making function is decentralized. For example, Poincelot and Wegmann (2005) notice that a high degree of decentralization requires diversifying the content of BSCs, pushing for the use of various indicators and including non-financial indicators. Therefore, our second hypothesis is formulated as follows:…”
Section: Research Hypothesesmentioning
confidence: 99%
“…La théorie de l'agence a été développée en 1976 par Jensen et Meckling. Nombreux sont les travaux (Solle et Rouby, 2003 ;Dambrin et Laning, 2008 ;Simons, 1990 ;Lorino,2001 ;Poincelot et Wegmann, 2005) qui associent la performance à la notion d'apprentissage. C'est pour cette raison que Lorino (2001) indiquait que, par opposition au contrôle de gestion traditionnel souvent structuré autour des centres de coûts, le pilotage moderne de l'organisation intègre la dimension de l'apprentissage organisationnel comme caractéristique essentielle de la performance construite collectivement à travers l'action collective.…”
Section: Apport De La Théorie De L'agenceunclassified
“…Research issues could be conducted through many angles. The non-financial information research issues include, inter alia, audit-modes and strategy and corporate governance to examine the credibility of non-financial information (O'Dwyer, 2011;O'Dwyer et al, 2011;Gillet-Monjarret & Martinez, 2012;Rivière-Giordano, 2007;Olson, 2010;Depoers, 2010) and to investigate the linkage between non-financial information attributes and management and control (Janicot, 2007;Berthelot et al, 2003;Essid & Berland, 2011;Poincelot and Wegmann, 2005;Karim et al, 2018;Ikram et al, 2019). All of these themes and issues as abovementioned could also be applied in sharia-compliant firms in countries and institutions either adopting or not yet adopting AAOIFI.…”
Section: Future Accounting Research Opportunities From a Convergence Framework Between Non-financial Information And Islamic Accounting Imentioning
confidence: 99%